Meningkatkan Mutu Pendidikan Melalui Peningkatan Kualitas Personal, Profesional, dan Strategi Rekrutmen Guru - Susanto, Aris; Haryati, Titik (Faculty Of Education, 2024)
The aim of writing this paper is to explain the importance of the role of teachers in improving the quality of education in Indonesia, especially facing the era of industrial revolution 4.0. It cannot be denied that the quality of teachers in Indonesia is still very low. The low quality of teachers in Indonesia is caused by factors, namely teachers' views about their profession that are still inaccurate, teacher qualifications that do not have a bachelor's degree, low levels of professional development and research programs, and teacher recruitment methods that are not yet effective. The research method used in this paper is library research by presenting arguments from the results of the literature review and the author's thoughts. The research results show that the quality of education in Indonesia can be achieved through three things, firstly increasing teachers' understanding of their duties and calling in the world of education continuously through Professional Development programs, and school mentoring. Second, proper supervision and implementation of UU No 14 tahun 2005 concerning teachers and lecturers. The government must collaborate with the private sector and universities to form research forums to improve the professional quality of teachers. Third, to improve teacher recruitment strategies that are not yet effective, the government and school leaders must apply the principle of accuracy in recruitment, namely accuracy between individuals and organizations, between teachers and schools, between teachers and students, as well as accuracy between teacher qualifications and teaching context.